2012
DOI: 10.1039/c2an35933b
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanoparticles intermediate layer in solid-state selective electrodes

Abstract: A platinum nanoparticles (PtNPs) layer is used for the first time as an ion-to-electron transducer in a solid-state ion-selective electrode (SC-ISE). The electrode was prepared by adding the PtNPs as an intermediate layer between the ionophore-doped solvent polymeric membrane and the electrical conductor. The PtNPs layer was characterized by high resolution transmission electron microscopy, selected area electron diffraction and X-ray photoelectron spectroscopy. The stability of the electrical potential of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…On the one hand, the diameter of the high-frequency semicircle, which equals the bulk membrane resistance coupled with the contact resistance between the GC substrate and the PVC membrane, was decreased from 0.19 MV to 0.11 MV by using LCPT transducer. On the other hand, the low-frequency response can be related to an interfacial charge-transfer from the GC/PVC interface and to the diffusion processes in the ISEs [21]. It seems that the ion-to-electron transduction processes proceed properly between the LCPT layer and PVC membrane as a larger low-frequency semicircle was observed arising from a small capacitance at the ''blocked'' interface GC/PVC membrane in CWEs.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the diameter of the high-frequency semicircle, which equals the bulk membrane resistance coupled with the contact resistance between the GC substrate and the PVC membrane, was decreased from 0.19 MV to 0.11 MV by using LCPT transducer. On the other hand, the low-frequency response can be related to an interfacial charge-transfer from the GC/PVC interface and to the diffusion processes in the ISEs [21]. It seems that the ion-to-electron transduction processes proceed properly between the LCPT layer and PVC membrane as a larger low-frequency semicircle was observed arising from a small capacitance at the ''blocked'' interface GC/PVC membrane in CWEs.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research reported that both platinum nanoparticles and carbon black used as an intermediate layer in solid contact electrodes decreased the total resistance of the electrode (Paczosa-Bator 2012; Paczosa-Bator et al 2012). Additionally, these materials improve a number of metrological parameters of sensors such as the potential reversibility and long term potential stability in both single (Paczosa-Bator 2012, 2014Paczosa-Bator et al 2012) and multi-electrode configuration (PaczosaBator et al 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, these materials improve a number of metrological parameters of sensors such as the potential reversibility and long term potential stability in both single (Paczosa-Bator 2012, 2014Paczosa-Bator et al 2012) and multi-electrode configuration (PaczosaBator et al 2014). Furthermore, using a composite combination of these two materials (platinum nanoparticles deposited on carbon black at 10 wt%) as the intermediate layer resulted in further improvement of analytical parameters (Paczosa-Bator et al 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, some of these SC-ISEs suffer from problems of the formation of water layers [7] and the interferences from oxygen, carbon dioxide and light [8]. On the other hand, nanostructured materials, mainly based on carbon (e.g., carbon nanotubes [9], colloid-imprinted mesoporous carbon [10], graphene [11], and fullerene [12]) and noble metals (e.g., nanoporous gold film [13] and platinum nanoparticles [14]), have been reported as ion-to-electron transducers owing to their special physicochemical properties. It has been shown that the large interface area between nanostructured materials and the ISM leads to a high double-layer capacitance, thus minimizing the potential drift.…”
Section: Introductionmentioning
confidence: 99%